Anatomical Variations on Routine CT Scans Observed in the Paranasal Sinuse - Ahmad Bin Khalid, Ayesha Siddiqa, Syed Imran Haider, Gohar Alam, Nadeem Akram Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the frequency of anatomical variants on routine CT scan observed in the paranasal sinus. Stud Design: Cross-sectional Place and Duration: The study was conducted at Radiology department of Jinnah Hospital, Lahore for the duration of nine months from January 2021 to September 2021. Methods: There were 90 sinus patients of both genders with ages 20-55 years in this study. Cases were recruited after informed written permission was obtained and data such as gender and BMI were collected. The prevalence of various anatomical variations of the sinonasal cavities was determined based on the results of the CT scans. Anatomical differences between individuals with low to no apparent imaging evidence of rhinosinusitis vs those with clinically substantial radiologic evidence of rhinosinusitis were examined in this study. SPSS 21.0 was used to analyze complete data. Results: Among 90 cases, the majority of the patients were males 63 (70%) and 27 (30%) were females with mean age 33.41±8.56 years and mean BMI 23.22 ±5.31 kg/m2. According to Kero’s classification to determine the difference in olfactory fossa depth, most of the patients 62 (68.9%) were in type II, 20 (22.2%) in type I and 8 (8.9%) in type III. In accordance with anatomical variation, we found that most of the patients 65 (72.2%) had deviated nasal septum (DNS) followed by agger nassi cells in 61 (67.8%) cases and concha bullosa in 35 (38.9%) cases. Conclusion: We concluded in this study that the prevalence of anatomical variants among patients of paranasl sinus was higher in which the majority of the patients had deviated nasal septum and agger nassi cells.